Towards Sensor-Based Health Monitoring Systems for Bridge Decks: A Full-Depth Precast Deck Panels Case Study - Osama Y. Abudayyeh; Joseph Barbera; Ikhlas Abdel-Qader; Hubo Cai; Eyad Almaita (Advances in Civil Engineering)
Traffic and variable loading conditions greatly influence the performance, durability, and safety of a bridge structure throughout its service life. Continuous monitoring can provide the basis for determining the deterioration rate and for estimating the remaining service life, thus assisting in making important decisions regarding bridge maintenance. This paper presents the design and implementation of a health monitoring system for condition assessment of full-depth precast concrete bridge deck, which was developed for the Parkview Bridge in Kalamazoo, Michigan. This system is composed of a remotely accessible on-site data acquisition system and a sensor network of vibrating wire strain gauges to monitor strain and temperature over given time increments. The system relies on the sensor network embedded in the bridge deck to gather static performance data under different loading conditions to provide condition assessment by collecting, storing, analyzing, and reporting relevant performance data over time. The paper presents a practical case study that mainly focuses on describing the initial steps in the development of the sensor network system, namely, the design (system architecture and data structures) and construction along with examples of how the data is acquired, organized, presented, and analyzed, keeping in mind that the bridge is still early in its life-cycle and has not yet experienced any structural problems.